The Effect Of Compaction Temperatures On The Marshall Properties Of Asphaltic Concrete - Zainal Ariffin, Azree Farees (IRC, 2016)
Asphaltic concrete can caused significant problems if using an inappropriate compaction temperature. Asphalt mixture usually loses their temperature during transportation and when laying down to be compacted. Temperature controls asphalt mixture viscosity which affect its ability to coat and provide adequate lubrication for aggregates and slides with each other and pack into dense mass during compaction. Compaction is one of major issue and an important criteria for asphaltic concrete process. At road construction site in Malaysia, the lowering compaction temperature are caused by transportation of mix, weather, and other factor that cannot be minimized.